Photovoltaic properties of ferroelectric ceramic thin films - Tan, Kee Sing. (2010)
The potential of using ferroelectric materials in applications such as sensors, transducers and micro-actuators has always been an area of intense research. In light of the increase in public awareness of the adverse effect of prolonged UV exposure, there is a need for the development of a low cost UV detector. Conventional semiconductor based UV detectors either requires expensive processing techniques or are sensitive to wavelengths in the visible region. Thus, an alternative method to realize UV detection is through the utilization of the photovoltaic property of ferroelectric thin film PLZT due to its corresponding bandgap around UV wavelengths.